La predicazione cappuccina per le quarantore e un sermonario annotato della fine del Seicento - Bino, Carla M. (Drammaturgia, 2021)
The essay explores the dramatic and performative dimension of the Forty Hours Devotion – one of the most important liturgical services of the Counter-Reformation – promoted by Capuchin Friars Minor between the 16th and 17th centuries. The first part summarizes the salient steps that marked the emergence of a precise system of celebration developed by the Order, highlighting those elements that made it original in choice of time, organization and, above all, detailed meditation practice. The second part is devoted to those changes that took place in the 17th century. Particular attention is dedicated to the new Baroque dramaturgy of the devotion: centered on the sermon, it was transformed from an interior ‘theatre of contrition’ into a ‘spectacle of penitence and conformation’. Lastly, the third part proposes an interpretation of Ultimi colpi al cuore de’ peccatori, written by Capuchin Domenico de Sancto da Francavilla in 1694. This sermon collection – in vernacular and with printed margin notes on gestures and actions for the preacher – is a unique example of rhetorical dramaturgy, almost a playscript for an actor.